Soil Nutrient Balance and Soil Fertility Status under the Influence of Fertilization in Maize-Wheat Cropping System in Nepal - Nabin Rawal; Keshab Raj Pande; Renuka Shrestha; Shree Prasad Vista (Applied and Environmental Soil Science)
Soil nutrient balance is affected by nutrient management in crops. A poor nutrient management technique results in an imbalance in the soil nutrient status which could have a long-term negative impact on crop production. The current study was carried out to assess the effect of different rates of nitrogen (N), phosphorus (P), and potassium (K) on soil nutrient balance in a maize-wheat cropping system in Cambisols of Khumaltar, Lalitpur, Nepal during 2019/20 and 2020/21. The experiment included three-factor randomized complete block design with three doses of each N, P, and K which was replicated three times. There was a remarkable change in soil pH, soil organic carbon (SOC), and total N, P, and K contents of soil over a period of time with the application of different doses of NPK. Soil pH changed from 5.98 to 5.53, SOC increased from 11.7 to 16.8 g·kg−1, total N decreased from 1264 to 1177 mg·kg−1, available P2O5 declined from 214 to 63.6 mg·kg−1, and available K2O decreased from 71.7 to 24.8 mg·kg−1 with varying rates of NPK after four cropping seasons. Furthermore, partial, apparent, and net N, P, K balance were predominantly negative in all the fertilizer treatments, but the magnitude was lower under higher nutrient rates and positive partial N balance was noticed in higher N levels. The depletion of native P and K pools even at higher application rates was attributed to higher crop removal over time as compared to inputs. Therefore, continuous application of balanced fertilizers is crucial in maintaining the fertility of soil and productivity of crops.